HUBUNGAN ANTARA KESIAPAN DAN KEBERHASILAN TOILET TRAINING PADA ANAK USIA TODDLER DI TEMPAT PENITIPAN ANAK (TPA) WILAYAH KECAMATAN GUNUNG ANYAR SURABAYA - Ernawati, Dwi (Politeknik Negeri Madura, 2021)
The success of toilet training for toddlers can be identified when a child cancontrol the external urinary sphincter. It can be achieved by physical readiness, mentaland child’s psychological, and parental readiness to begin the toilet training practice. Thisstudy aims to analyze the correlation between the readiness and success of toilet trainingfor toddlers in one of the daycare services in Gunung Anyar. Methods : In this research,the population was 78, with 66 respondents using a simple random sampling technique. Across-sectional technique design was applied, and The researcher collected the data usinga questionnaire. In addition, the data were analyzed with Spearman Rho. Results : Theanalysis showed that there was a relationship between physical readiness and the successof toilet training (? = 0.001). The relationship between mental readiness and toilet trainingsuccess (? = 0.001). The relationship between psychological readiness and toilet trainingsuccess (? = 0.001). Relationship between parental readiness and toilet training success(? = 0.001). It can be concluded that there is a relationship between the readiness andsuccess of toilet training for toddlers. Conclusions : This research implies that childrenwill have physical, mental, and psychological readiness, and parents can support thesuccess of toilet training in toddlers